Magritte's marvellous hat - D.B.Johnson (Macmillan Education Australia Pty Ltd, 2013)
hen painter Magritte, depicted as a well-dressed, floppy-eared dog, buys a playful--and mysterious--hat, his painting enjoys a burst of creativity. Inspired by the art of French surrealist painter Rene Magritte